Supramolecular Additive-Initiated Controlled Atom Transfer Radical Polymerization of Zwitterionic Polymers on Ureido-pyrimidinone-Based Biomaterial Surfaces - Ippel, Bastiaan D. (Macromolecules, 2020)
[Image: see text] Surface-initiated controlled radical polymerization is a popular technique for the modification of biomaterials with, for example, antifouling polymers. Here, we report on the functionalization of a supramolecular biomaterial with zwitterionic poly(sulfobetaine methacrylate) via atom transfer radical polymerization from a macroinitiator additive, which is embedded in the hard phase of the ureido-pyrimidinone-based material. Poly(sulfobetaine methacrylate) was successfully polymerized from these surfaces, and the polymerized sulfobetaine content, with corresponding antifouling properties, depended on both the macroinitiator additive concentration and polymerization time. Furthermore, the polymerization from the macroinitiator additive was successfully translated to functional electrospun scaffolds, showing the potential for this functionalization strategy in supramolecular material systems.